2011
DOI: 10.1111/j.1600-6143.2010.03424.x
|View full text |Cite|
|
Sign up to set email alerts
|

The Long-Term Quality of Life of Living Kidney Donors: A Multicenter Cohort Study

Abstract: Previous studies that described the long-term quality of life of living kidney donors were conducted in single centers, and lacked data on a healthy nondonor comparison group. We conducted a retrospective cohort study to compare the quality of life of 203 kidney donors with 104 healthy nondonor controls using validated scales (including the SF36, 15D and feeling thermometer) and author-developed questions. Participants were recruited from nine transplant centers in Canada, Scotland and Australia. Outcomes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
87
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(96 citation statements)
references
References 32 publications
7
87
0
2
Order By: Relevance
“…This finding is similar to the satisfying effects of kidney donation discussed in some recent studies. [11][12][13] In our study, we revealed a high incidence of obesity in our donor group. In a recent epidemiologic study in Turkey, obesity prevalence was reported to be 44% in women and 27% in men, which may reflect that obesity is an endemic problem in Turkey involving the donor group of our study.…”
Section: Discussionsupporting
confidence: 51%
“…This finding is similar to the satisfying effects of kidney donation discussed in some recent studies. [11][12][13] In our study, we revealed a high incidence of obesity in our donor group. In a recent epidemiologic study in Turkey, obesity prevalence was reported to be 44% in women and 27% in men, which may reflect that obesity is an endemic problem in Turkey involving the donor group of our study.…”
Section: Discussionsupporting
confidence: 51%
“…Although both physical health and mental health summary scores have been shown to be excellent in a large population of kidney donors [14], they only indirectly reflect the social and psychological impact of kidney donation over the long-term. Validated scores, such as the SF-12 and SF-36 scores, are useful methods for comparing the quality of life regarding physical and mental health status between various medical conditions, including kidney donation [19], but do not specifically address questions related to living kidney donation [8,9]. Even though the questionnaire used in our study is not validated, it integrates univocal and critical questions regarding the psychological and social consequences of kidney donation, which relate closely to each donor.…”
Section: Discussionmentioning
confidence: 99%
“…Most kidney donors experience psychosocial benefits, including improved self-esteem and donor-recipient relationships (1)(2)(3)(4)(5); likewise, most report no regrets (6,7) and reaffirm their decision to donate (3,(8)(9)(10)(11)(12)(13). However, these experiences are not universal.…”
Section: Introductionmentioning
confidence: 99%